POLA KEPEMIMPINAN DAN SISTEM MANAJEMEN PENDIDIKAN DI BEBERAPA NEGARA PERSEMAKMURAN: SUATU KAJIAN ANALISA PERBANDINGAN - Afdhal Afdhal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2010)
Leadership pattern and management system will determine education quality of a country. The commonwealth countries have applied such pattern and system which are similar to their educational management. Australia, Canada, and England, for example, have reformed their educational system. As a result, they can produce good quality of education. This article analyzes leadership pattern and management system in the three mentioned commonwealth countries. By conducting comparison analysis, this situation is expected to be a guidance and example for educational management in Indonesia which in turn will improve the education quality.Kata kunci: pola kepemimpinan pendidikan, sistem manajemen pendidikan